PENGARUH KOMPENSASI, DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN (STUDI PADA NOZZ HOTEL SEMARANG) - Indah Lestari, 13.05.51.0096; Rahayuningsih, Sri (Students Journal of Economic and Management, 2017)
This study analyzed the effect of compensation,work discipline and cempetency .object of study in this paper is the Nozz Hotel Semarang .The sampling technique in his research is to use simple random sampling (random) semple of 53 respondents as a data collection method using a questionnairen (questionnaire) by distributing a list of questions to the respondent inorder to obtain informasion .the research objective wash formulated to dettermine the effect of compensation ,work discipline ,and competency of employe performance.The data were analyzed using factor analysis to tast the validity of the question items ,Cronbeach alpa formula to test the reliability of each of the research are : (1) compensation has a positive and significant impact influence on employee performance. (2) work dicipline has a positive and significant influence on employee performance. (3) competence has a positive and significant influence on employee performance.Â Keywords : Work Compensation, Discipline, Competence, and Performance